In the Wake of the Manuscripts of Bernarde of Naples - Gaga Shurgaia (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2011)
The paper deals with the history of the manuscript materials of Bernarde of Naples, a Capuchin monk on a mission to Georgia in 1670-1677. In particular, it has transpired that originally the materials were preserved in the library of the monastery of Capuchins, and on 7 February 1936 they were moved to the National Royal Library (at present National Library of Naples), where they are preserved to the present day, under the call number “XX. 122”. A study of the lists drawn up by various scholars in the 18th-20th centuries, has shown that in 1886-1936 one Georgian manuscript of Bernarde of Naples was lost, which contained the “Romance” or the Georgian Fairy Tale “Baama”, an earliest, forty-page fragment of the so-called chronicle of “One Hundred Years” of the “Zhamtaaghmtsereli”, and “A small poem “Reskariani”.